Crescimento de cultivares de mamoneira em função da aplicação de boro, durante a formação de mudas - De Arruda Rodrigues, Helen Cristina [UNESP]; De Carvalho, Samuel Pereira; De Souza, Henrique Antunes [UNESP]; Jesus, Adriana Madeira Santos (My University, 2009)
It was objectified to quantify the initial growth of varieties of castor bean with boron fertilization. Had been tested to cultivate they AL-Guarani, Mirante 10 and Nordestina to the doses of 0; 0.25; 0.50; 0.75 and 1.0 mg kg -1 of B in controlled environment of greenhouse in the Sector of Cafeicultura of the Department of Agriculture of the UFLA. The characteristics valued were: height of plants, length of roots, leaf number, diameter of stem, mass of dry substance (MS) of leafs, of stem, the root and total. To cultivate Mirante 10 it was the one that got minor growth of the system of root. For leaf number to cultivate AL-Guarani it was superior to Mirante 10 and Nordestina. Also to cultivate better AL-Guarani if it detached how much to the production of total mass of MS, while to cultivate Mirante 10 produced more mass of MS than Nordestina.
Growth to cultivate of castor bean with aplication of boron, during the formation of changes
Keywords: Fertilization; Greenhouse; Ricinus communis L.